Application of Machine Learning in Microbiology - Qu, Kaiyang; Guo, Fei; Liu, Xiangrong; Lin, Yuan; Zou, Quan (Frontiers in Microbiology, 2019)
Microorganisms are ubiquitous and closely related to people’s daily lives. Since they were first discovered in the 19th century, researchers have shown great interest in microorganisms. People studied microorganisms through cultivation, but this method is expensive and time consuming. However, the cultivation method cannot keep a pace with the development of high-throughput sequencing technology. To deal with this problem, machine learning methods have been widely applied to the field of microbiology. Literature reviews have shown that machine learning can be used in many aspects of microbiology research, especially classification problems, and for exploring the interaction between microorganisms and the surrounding environment. In this study, we summarize the application of machine learning to microbiology.